Calpain 3 and CaMKIIβ signaling are required to induce HSP70 necessary for adaptive muscle growth after atrophy. (8th March 2018) - Kramerova, Irina; Torres, Jorge A; Eskin, Ascia; Nelson, Stanley F; Spencer, Melissa J
Abstract: Mutations in CAPN3 cause autosomal recessive limb girdle muscular dystrophy 2A. Calpain 3 (CAPN3) is a calcium dependent protease residing in the myofibrillar, cytosolic and triad fractions of skeletal muscle. At the triad, it colocalizes with calcium calmodulin kinase IIβ (CaMKIIβ). CAPN3 knock out mice (C3KO) show reduced triad integrity and blunted CaMKIIβ signaling, which correlates with impaired transcriptional activation of myofibrillar and oxidative metabolism genes in response to running exercise. These data suggest a role for CAPN3 and CaMKIIβ in gene regulation that takes place during adaptation to endurance exercise. To assess whether CAPN3- CaMKIIβ signaling influences skeletal muscle remodeling in other contexts, we subjected C3KO and wild type mice to hindlimb unloading and reloading and assessed CaMKIIβ signaling and gene expression by RNA-sequencing. After induced atrophy followed by 4 days of reloading, both CaMKIIβ activation and expression of inflammatory and cellular stress genes were increased. C3KO muscles failed to activate CaMKIIβ signaling, did not activate the same pattern of gene expression and demonstrated impaired growth at 4 days of reloading. Moreover, C3KO muscles failed to activate inducible HSP70, which was previously shown to be indispensible for the inflammatory response needed to promote muscle recovery. Likewise, C3KO showed diminished immune cell infiltration and decreased expression of pro-myogenic genes. These data support a role for CaMKIIβ signaling in induction of HSP70 and promotion of the inflammatory response during muscle growth and remodeling that occurs after atrophy, suggesting that CaMKIIβ regulates remodeling in multiple contexts: endurance exercise and growth after atrophy.